2021
DOI: 10.1029/2020jc016610
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Scattering and Backscattering in Relation to the Nature of Particles in the Red Sea

Abstract: The ocean contains a large variety of suspended particles that cover a broad size range, from 0.1 nm to 1 mm, and vary in origin (i.e., biogenic or terrestrial), shape and internal composition (i.e., refractive index; Stramski et al., 2004). The pool of suspended particles is often divided into non-algal particles and phytoplankton. Non-algal particles include: (1) heterotrophs (i.e., bacteria, viruses and zooplankton), (2) non-living organic detritus produced by zoo-and phyto-plankton (i.e., fecal pellets, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 81 publications
2
10
0
Order By: Relevance
“…Our values of were found to vary over the season, with a median value of 0.00035 m −1 (see Supplementary Figure S6 ), consistent with the ranges reported in Kheireddine et al. ( 2021 ) and globally by Bellacicco et al. ( 2019 ) at 700 nm.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our values of were found to vary over the season, with a median value of 0.00035 m −1 (see Supplementary Figure S6 ), consistent with the ranges reported in Kheireddine et al. ( 2021 ) and globally by Bellacicco et al. ( 2019 ) at 700 nm.…”
Section: Resultssupporting
confidence: 90%
“…Using a large dataset of scattering and absorption measurements collected in the Red Sea, Kheireddine et al (2021) recently demonstrated that the background backscattering coefficient 𝐴𝐴 (𝑏𝑏 𝑘𝑘 𝑏𝑏𝑏𝑏 ) is likely dominated by non-algal particles. Our values of 𝐴𝐴 𝐴𝐴 𝑘𝑘 𝐴𝐴𝑏𝑏 were found to vary over the season, with a median value of 0.00035 m −1 (see Supplementary Figure S6), consistent with the ranges reported in Kheireddine et al (2021) and globally by Bellacicco et al (2019) at 700 nm. Higher 𝐴𝐴 𝐴𝐴 𝑘𝑘 𝐴𝐴𝑏𝑏 values were found during the winter period (Figure 5 and Supplementary Figure S6), possibly reflecting seasonal variation in the concentrations of non-algal particles (Bellacicco et al, 2019(Bellacicco et al, , 2020.…”
Section: Particle Backscattering Model Resultsmentioning
confidence: 99%
See 3 more Smart Citations